STRENGTHENING THE CAPABILITIES OF ROOM HEADS IN IMPLEMENTING THE EARLY WARNING SCORE (EWS) SYSTEM AT PINDAD TUREN HOSPITAL - Indasah, Indasah; Rodli, Muhammad (HEARTY, 2025)
Early Warning Scoring (EWS) is a clinical instrument designed to detect early deterioration in a patient's medical condition by monitoring vital signs such as pulse, blood pressure, and respiratory frequency. This early detection allows health workers to carry out medical interventions quickly and precisely, thereby increasing the chances of patient safety. However, the implementation of EWS at Pindad Turen Hospital is still not running optimally. The main problem found was the lack of integration in the assessment and recording of EWS scores by health workers, which resulted in delays in clinical decision-making. This study aims to analyze the level of EWS utilization in the hospital through outreach and training activities. Before the training, a pretest was carried out, and after the training, a posttest was carried out to measure the increase in knowledge of health workers. The results show that there is no uniform standard for writing EWS scores. As a form of intervention, the supervision function is strengthened as cues to action whose role is to encourage and guide health workers in the correct implementation of EWS. Through the active involvement of supervision, it is hoped that there will be increased consistency and accuracy in the assessment and recording of EWS scores by nurses in each service unit.